1999
DOI: 10.1007/s004180050421
|View full text |Cite
|
Sign up to set email alerts
|

Localization of liver myofibroblasts and hepatic stellate cells in normal and diseased rat livers: distinct roles of (myo-)fibroblast subpopulations in hepatic tissue repair

Abstract: Previous in vitro studies indicated that hepatic stellate cells (HSC) and rat liver myofibroblasts (rMF) have to be regarded as different cell populations of the myofibroblastic lineage with fibrogenic potential. Employing the discrimination features defined by these studies the localization of HSC and rMF was analyzed in diseased livers. Normal and acutely as well as chronically carbon tetrachloride-injured livers were analyzed by immunohistochemistry and by in situ hybridization. In normal livers HSC [desmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
1
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(157 citation statements)
references
References 29 publications
7
145
1
4
Order By: Relevance
“…MFs are the principal cells located within the scar tissue (Knittel et al 1999b). Thy-1 expression has the potential to distinguish between aHSC and rMF in vitro Dudas et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…MFs are the principal cells located within the scar tissue (Knittel et al 1999b). Thy-1 expression has the potential to distinguish between aHSC and rMF in vitro Dudas et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…At one time the origin of the myofibroblasts in liver injury was obscure, because "fibroblasts" are rare in normal liver, consisting only of a few that reside in the periportal stroma (Knittel et al, 1999). Initial clues derived from histological studies that found "fat-storing cells" (now termed hepatic stellate cells, HSC) in the vicinity of injury and fibrosis (Kent et al, 1976).…”
Section: Hepatic Stellate Cell (Hsc) Activationmentioning
confidence: 99%
“…To date, there are no FDA approved antifibrotic drugs (2). Fibrosis is characterized by excessive production of extracellular matrix (ECM) components, especially type I and III fibrillar collagens within the perivascular and interstitial space of tissues (3,4). † This work was supported by a grant RO1 DK064633 from the NIH and USPHS grant 47379.…”
Section: Introductionmentioning
confidence: 99%